Redistribution and fiscal policy - Juan F. Rubio-Ramirez (Federal Reserve Bank of Atlanta, 2002)
This paper studies the optimal behavior of a democratic government in its use of fiscal policies to redistribute income. I present a stochastic dynamic general equilibrium model with heterogeneous agents to analyze (1) the differences between the effects on the optimal tax rate of permanent and nonpermanent perturbations and (2) the relationship between initial inequality and both steady-state levy and income distribution. In addition, the optimal fiscal policy for the transition is calculated. The analysis leads me to three main conclusions. First, there are no important differences between how taxes respond to a permanent or nonpermanent perturbation. Second, the initial inequality has a huge effect on both actual levy and actual income distribution. And finally, the Chari, Christiano, and Kehoe (1992) result, i.e., taxes on labor are roughly constant over the business cycle, holds only if the productivity ratio is constant. In addition, the model implies a positive correlation between inequality and tax rate, just as in the basic literature.
Keywords: 330; Taxation; Income distribution